Does oil consumption respond asymmetrically to oil price, exchange rate and income differentials? - Uche, Emmanuel; Ihezukwu, Veronica Adaku; Osunkwo, Folusho Olufunke Chinyere; Okoronkwo, Chijioke (Penerbit Universiti Kebangsaan Malaysia, 2021)
This study empirically evaluates the dynamic effects oil price, income and exchange rate on oil consumption in Algeria, Angola, Nigeria, South Africa, and Tunisia. Specifically, it tries to reveal the differential effects of rising and falling oil prices, economic prosperities and adversaries, as well as, exchange rate appreciations and depreciation on oil consumption in the selected countries. The current study relied on monthly data sourced from OPEC and IMF-IFS data banks and analyzed within the Nonlinear ARDL framework. The NARDL model traces asymmetry in macroeconomic relationships by isolating the effects of positive changes from negative changes. The empirical findings reveal that the effects of oil price deviations on oil consumption is asymmetric in the short-run in Angola and Tunisia, and in the long-run in Nigeria. Furthermore, income and exchange rate deviations affect oil consumption asymmetrically in Algeria, Nigeria, South Africa and Tunisia. However, exchange rate deviation does not have an asymmetric effect on oil consumption in Algeria. The overall implication of such asymmetric effects is that positive deviations could not offset negative deviations and vice-versa. Therefore, to guide against general welfare losses, policymakers should take cognizance of such nonlinear and asymmetric effects in their policy moderations.